Engineering Lithium Ions Embedded in NiFe Layered Double Hydroxide Lattices To Activate Laminated Ni2+ Sites as High‐Efficiency Oxygen Evolution Reaction Catalysts. Issue 32 (11th May 2020) - Sun, Zemin; Yuan, Mengwei; Shi, Kefan; Liu, Yuhui; Wang, Di; Nan, Caiyun; Li, Huifeng; Sun, Genban; Yang, Xiaojing
Abstract: NiFe layered double hydroxides (LDHs) have been denoted as benchmark non‐noble‐metal electrocatalysts for the oxygen evolution reaction (OER). However, for laminates of NiFe LDHs, the edge sites are active, but the basal plane is inert, leading to underutilization as catalysts for the OER. Herein, for the first time, light and electron‐deficient Li ions are intercalated into the basal plane of NiFe LDHs. The results of theoretical calculations and experiments both showed that electrons would be transferred from near Ni 2+ to the surroundings of Li +, resulting in electron‐deficient properties of the Ni sites, which would function as "electron‐hungry" sites, to enhance surface adsorption of electron‐rich oxygen‐containing groups, which would enhance the effective activity for the OER. As demonstrated by the catalytic performance, the Li−NiFe LDH electrodes showed an ultralow overpotential of only 298 mV at 50 mA cm −2, which was lower than that of 347 mV for initial NiFe LDHs and lower than that of 373 mV for RuO2 . Reasonable intercalation adjustment effectively activates laminated Ni 2+ sites and constructs the electron‐deficient structure to enhance its electrocatalytic activity, which sheds light on the functional treatment of catalytic materials. Abstract : Eat up ! In laminates of NiFe layered double hydroxides (LDHs), the edge sites are active, but the basal plane is inert, leading to underutilization as catalysts for the oxygen evolution reaction (OER). An "electron‐hungry" Li−NiFe LDH has been prepared as an effective and robust OER electrocatalyst.